Macromol. Rapid Commun. 9/2017. Issue 9 (May 2017) - Solleder, Susanne C.; Schneider, Rebekka V.; Wetzel, Katharina S.; Boukis, Andreas C.; Meier, Michael A. R.
Abstract : Back Cover: Synthesis strategies towards monodisperse, sequencedefined macromolecules are presented in this review, including conjugated and non‐conjugated linear oligomers. Hence, sequencedefined macromolecules containing defined monomer sequences as well as monodisperse oligomers with a regulated monomer sequence are considered. Further details can be found in article number1600711 by Susanne C. Solleder, Rebekka V. Schneider, Katharina S. Wetzel, Andreas C. Boukis, and Michael A. R. Meier*.